An Examination of EFL Undergraduates’ Writing Error Types and Frequency in WhatsApp Chat Messaging: Exploring Key Factors - Mohammad Owais Khan; Mohd Nazim; Ali Abbas Falah Alzubi (Qubahan Academic Journal)
English as a Foreign Language (EFL) undergraduates' writing has consistently attracted the attention of educational stakeholders, notably teachers. Studies have been conducted to address writing challenges in various contexts, including social media platforms. However, rare research is available to examine the specific types and frequency of writing errors committed by EFL undergraduates while using WhatsApp, particularly in the context of Najran University. Therefore, the current study aimed to examine the types of errors and their frequency that EFL students commit in WhatsApp chat messages. Following a descriptive research design, this study used WhatsApp chat messaging samples and conducted semi-structured interviews with a sample of 40 English undergraduates. The content analysis of students' chat messages on WhatsApp indicated errors in spelling, verb tense, capitalization, noun number, and punctuation. Among these, the most frequent error was spelling. Additionally, the analysis of semi-structured interviews identified factors responsible for these errors, including excessive dependence on abbreviations and shortcuts, lack of familiarity with formal and informal communication, inadequate attention to grammar standards, limited exposure and practice with English language writing conventions, unfamiliarity with the formatting choices in WhatsApp, and interruptions from notifications and other conversations. Based on the findings, suggestions and recommendations are presented to address the writing issues of EFL undergraduates.